Usability Testing of a Sensor-Controlled Digital Game to Engage Older Adults with Heart Failure in Physical Activity and Weight Monitoring - Radhakrishnan, Kavita (Appl Clin Inform, 2020)
Background  Poor self-management of heart failure (HF) has contributed to poor health outcomes. Sensor-controlled digital games (SCDGs) integrates data from behavior-tracking sensors to trigger progress, rewards, content, and positive feedback in a digital game to motivate real-time behaviors. Objectives  To assess the usability of an SCDG prototype over a week of game-playing among 10 older adults with HF in their homes. Methods  During initial play, participants' SCDG experiences were observed in their homes using a checklist based on the seven-item Serious Game User Evaluator (SeGUE) instrument. After a week of game-playing, participants completed a survey guided by the Intrinsic Motivation Inventory, to provide their perceptions of the SCDG's usability. Qualitative analysis via semistructured interview-derived themes on experiences playing the SCDG, perceptions regarding engaging with the SCDG, and any usability issues encountered. Results  Ten HF participants (50% women and 50% White) played the SCDG for an average of 6 out of 7 days. Nine found the SCDG to be interesting, satisfying, and easy to play. The average step count over a week was 4,117 steps (range: 967–9,892). Average adherence with weight monitoring was 5.9 days in a week. Qualitative analysis yielded outcomes regarding attitudes toward SCDG, and barriers and facilitators that influenced participants' engagement with the SCDG. Conclusion  To the best of the authors' knowledge, this usability and feasibility study is the first to report an SCDG designed to improve HF self-management behaviors of older adults in their homes. Future research should consider several issues, such as user profiles, prior game-playing experiences, and network conditions most suitable for connected health interventions for older adults living in the community.